Synthesis and Characterization of Fe‐Phthalocyanine‐Based Metal–Organic Framework - Hiroto Oi; Momoka Isobe; Riko Kishikawa; Fumiya Abe; Norihiro Morishita; Shunsuke Takagi; Shota Nakayama; Kaname Kanai (Advanced Physics Research)
Abstract This paper reports the successful synthesis of Fe‐phthalocyanine‐based metal‐organic framework (FePc‐MOF) by simple thermal polymerization. FePc‐MOF is a promising candidate for Lieb lattice, which is a type of Dirac materials with two independent sites in a square unit cell, and it is theoretically predicted to have a unique electronic structure featuring both a Dirac band and a flat band near the Fermi level. The prepared samples exhibit the structure of FePc‐MOF, as confirmed by X‐ray diffraction, Fourier transform infrared spectroscopy, and transmission electron microscopy. The FePc‐MOF pellet demonstrates electrical conductivity approximately a thousand times higher than that of its precursor, octacyano‐Fe‐phthalocyanine. This significant increase in electrical conductivity compared to the precursor indicates that FePc‐MOF has a 2D π‐electron system with a FePc‐based framework and is consistent with the prediction that FePc‐MOF is a semiconductor with a narrow energy gap due to its Lieb lattice‐like structure. The synthesis method developed in this study is expected to advance fundamental research on Lieb lattices as new electronic and magnetic functional materials.